Root vacuolar sequestration and suberization are prominent responses of Pistacia spp. rootstocks during salinity stress. (19th May 2021) - Zhang, Shuxiao; Quartararo, Alessandra; Betz, Oliver Karl; Madahhosseini, Shahab; Heringer, Angelo Schuabb; Le, Thu; Shao, Yuhang; Caruso, Tiziano; Ferguson, Louise; Jernstedt, Judy; Wilkop, Thomas; Drakakaki, Georgia
Abstract: Understanding the mechanisms of stress tolerance in diverse species is needed to enhance crop performance under conditions such as high salinity. Plant roots, in particular in grafted agricultural crops, can function as a boundary against external stresses in order to maintain plant fitness. However, limited information exists for salinity stress responses of woody species and their rootstocks. Pistachio ( Pistacia spp.) is a tree nut crop with relatively high salinity tolerance as well as high genetic heterogeneity. In this study, we used a microscopy‐based approach to investigate the cellular and structural responses to salinity stress in the roots of two pistachio rootstocks, Pistacia integerrima (PGI) and a hybrid, P. atlantica x P. integerrima (UCB1). We analyzed root sections via fluorescence microscopy across a developmental gradient, defined by xylem development, for sodium localization and for cellular barrier differentiation via suberin deposition. Our cumulative data suggest that the salinity response in pistachio rootstock species is associated with both vacuolar sodium ion (Na + ) sequestration in the root cortex and increased suberin deposition at apoplastic barriers. Furthermore, both vacuolar sequestration and suberin deposition correlate with the root developmental gradient. We observed a higher rate of Na + vacuolar sequestration and reduced salt‐induced leaf damage in UCB1 when compared to P. integerrima . In addition, UCB1 displayed higher basal levels of suberization, in both the exodermis and endodermis, compared to P. integerrima . This difference was enhanced after salinity stress. These cellular characteristics are phenotypes that can be taken into account during screening for sodium‐mediated salinity tolerance in woody plant species.